The Variety Of The Ethnic In Palembang At Dutch Colonial Period : The study of The Imbalance of Colonial government policy between the Arab and China (1825-1942) - Eva Febriani, Tyas Fernanda, Aris Cahyono & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
After the Palembang Darussalam Sultanate collapsed in 1825, the colonial governmenttook full control of the territory of the former of the sultanate. The colonial government madePalembang be a crowded city with many foreign visitors. It made Palembang to be the central ofeconomic matters of South Sumatra region at the time. The Foreigner who came to Palembang areChinese, Arabs and Europeans. They had different purposes such as selling and staying. With thesettlement of foreign immigrants in the city of Palembang, they must obey the rule of the governmentof colonial government. the Colonial Government gave different treatments for migrants inPalembang. The European became the first priority among other sellers. The Chinese and the arabswho were from different ethnics got imbalance policy. The Chinese was more special than arabs. TheChinese was regarded to be qualified enough for giving the profit to the colonial government. Besidethat the government thought that the arabs would impede for directness of colonial government inPalembang.Keywords: inequality, colonial, foreign entrants,